BDNF: the career of a multifaceted neurotrophin in spinal cord injury - Weishaupt, Nina; Blesch, Armin; Fouad, Karim (Experimental neurology, 2012)
Brain-derived neurotrophic factor (BDNF) has been identified as a potent promoter of neurite growth, a finding that has led to an ongoing exploration of this neurotrophin as a potential treatment for spinal cord injury. BDNF's many effects in the nervous system make it an excellent candidate for neuroprotective strategies as well as for promoting axonal regeneration, plasticity and re-myelination. In addition, neuronal activity and physical exercise can modulate the expression of BDNF, suggesting that non-invasive means to increase BDNF levels might exist. Nonetheless, depending on the location, amount and duration of BDNF delivery, this potent neurotrophin can also have adverse effects, such as modulation of nociceptive pathways or contribution to spasticity. Taken together, the benefits and possible risks require careful assessment when considering this multifaceted neurotrophin as a treatment option for spinal cord injury.
Gesehen am 09.05.2019